FINALCIAL LITERACY DAN PERILAKU KEUANGAN MAHASISWA (STUDI KASUS MAHASISWA STIE ‘YPPI’ REMBANG) - Dian Anita Sari (Sekolah Tinggi Ilmu Ekonomi YPPI Rembang, 2015)
Financial intelligence in the competition is absolutely necessary in today's modern society. Deemed necessary, due to the financial intelligence that includes how a person manages financial-owned well is capital to improve the welfare of each individual. This study intends to analyze the effect of learning in college and family financial education to student financial behavior, and the impact of the financial literacy of students to the financial behavior of students with student research object STIE 'YPPI' Rembang. Research shows that learning in higher education and financial education affect student financial literacy, while financial literacy have an impact on the financial behavior of the students. Additionally, financial literacy proved able to moderate learning in college and family financial education in student financial behavior.Keyword : Financial Literacy, Financial education, Financial behavior